The Effect of Work Motivation, Work Discipline, Work Environment and Job Training on Employee Performance at The Brantas Abipraya Employee Cooperative (KKBA) - Novita Sari, Minda Dian; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
This study aims to assess the impact of Work Motivation, Work Discipline, Work Environment, and Job Training on Employee Performance at the Brantas Abipraya Employee Cooperative (KKBA). The primary data source for this research consists of questionnaires distributed to 94 respondents affiliated with the Brantas Abipraya Employee Cooperative (KKBA). The sampling technique employed is non-probability sampling, specifically axial sampling, where data is collected from encountered sampling units. Data analysis involves multiple linear regression and hypothesis testing using t-statistics, with the results processed in SPSS 23 to examine regression coefficients. The partial findings of this research indicate that Work Motivation, Work Discipline, Work Environment, and Job Training each exhibit a positive and significant influence on Employee Performance at the Brantas Abipraya Employee Cooperative (KKBA).